2022
DOI: 10.1093/conphys/coac042
|View full text |Cite
|
Sign up to set email alerts
|

Integrating earthworm movement and life history through dynamic energy budgets

Abstract: Earthworms are considered ecosystem engineers and, as such, they are an integral part of the soil ecosystem. The movement of earthworms is significantly influenced by environmental factors such as temperature and soil properties. As movement may directly be linked to food ingestion, especially of endogeic species like Aporrectodea caliginosa, changes in those environmental factors also affect life history traits such as growth and reproduction.In our laboratory studies, earthworms showed a decrease in burrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The EAEs introduced here can be used to refine standard RA, and yet should be regarded as an interim solution as SPGs for soil organisms are concerned with biological entities, and hence require corresponding modeling endpoints like the population level (EFSA PPR Panel, 2017). As effect models are also becoming increasingly more available for RA purposes (Bart et al, 2021;Forbes et al, 2020;Gergs et al, 2022;Johnston et al, 2014aJohnston et al, , 2014bJohnston et al, , 2018Meli et al, 2013;Raimondo et al, 2021;Rakel et al, 2020;Reed et al, 2016;Roeben et al, 2020), an important next step is to integrate effect models into xOffFieldSoil, and so directly link them to the exposure module in required spatial and temporal resolutions. The outcome of xOffFieldSoil then provides biological AEs and their spatiotemporal scales directly addressing SPGs of off-field soil organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The EAEs introduced here can be used to refine standard RA, and yet should be regarded as an interim solution as SPGs for soil organisms are concerned with biological entities, and hence require corresponding modeling endpoints like the population level (EFSA PPR Panel, 2017). As effect models are also becoming increasingly more available for RA purposes (Bart et al, 2021;Forbes et al, 2020;Gergs et al, 2022;Johnston et al, 2014aJohnston et al, , 2014bJohnston et al, , 2018Meli et al, 2013;Raimondo et al, 2021;Rakel et al, 2020;Reed et al, 2016;Roeben et al, 2020), an important next step is to integrate effect models into xOffFieldSoil, and so directly link them to the exposure module in required spatial and temporal resolutions. The outcome of xOffFieldSoil then provides biological AEs and their spatiotemporal scales directly addressing SPGs of off-field soil organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, ecological modeling in combination with analytical measurements of chemical residues over the test period can help to understand the actual exposure that is experienced by the organism under investigation, once ecological models have been validated. The specific exposure of organisms to contaminants could be refined through simulation of realistic movement of the organisms in the soil profile over time and using toxicokinetic toxicodynamic modeling on the individual level (Forbes et al, 2021; Gergs et al, 2022; Roeben et al, 2020). However, Toschki et al (2020) showed long‐lasting effects of chemicals persisting after surface spray application on soil organisms living also in deeper soil layers.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
“…Milles et al, 2020;Rybicki et al, 2020), but they neglect detailed individual energetics, which are increasingly popular for single-species applications (e.g. Boult et al, 2018;Gallagher et al, 2021;Gergs et al, 2022;Malishev et al, 2018). While some metabolic fish community models have been presented (e.g.…”
Section: Introductionmentioning
confidence: 99%